Callous‐unemotional traits in children and mechanisms of impaired eye contact during expressions of love: a treatment target?. (9th October 2013) - Dadds, Mark R.; Allen, Jennifer L.; McGregor, Kimberley; Woolgar, Matthew; Viding, Essi; Scott, Stephen
<x xml:space="preserve">Abstract</x> Background We previously hypothesised that the early development of psychopathy is associated with a failure to attend to the eyes of attachment figures, and we have presented preliminary data from a parent–child 'love' scenario in support of this. Here, we confirm the association in a larger sample and test mechanisms of impaired eye contact during expressions of love in control and behaviourally disturbed children. Methods Oppositional defiant disorder children, assessed for callous‐unemotional (CU) traits, and controls, were observed in a brief interaction task where the mother was asked to show love to her child. Eye contact and affection were measured for each dyad. Results As predicted, there were no group differences in affection and eye contact expressed by mothers; levels of CU traits predicted low levels of eye contact towards their mothers across all groups of children. As expected, low eye contact was correlated with psychopathic fearlessness in their fathers, and maternal reports of negative feelings towards the child. Independent observations showed that child's behaviour largely drives the low eye contact associated with CU traits, and low eye contact was not associated with independent observations of the quality of attachment‐related behaviours in mothers. Conclusions Impaired eye contact is a unique characteristic of children with CU traits; these impairments are largely independent of maternal behaviour, but associated with psychopathic traits in the fathers. These impairments should be tested for functional significance and amenability to change in longitudinal and treatment studies.